Election campaigns to Stavropol City Duma in September – November 1919 - A. A. Chemakin (Гуманитарные и юридические исследования)
The article deals with elections to the Stavropol City Duma in autumn 1919. In that time the city was under control of Armed Forces of South Russia and the local White military administration working for a loyal Duma actively meddled in the race and put on moderate and rightwing political forces which put forward straightway several lists of candidates (neighborhood guardianships, burghers and house owners). A main opponent of authorities was a socialist block consolidating Socialist-Revolutionaries, Mensheviks and a number of public organizations. The list of “progressive voters” was in between. Elections on the 15th of September were won by socialists, but the district court invalidated the voting returns on the pretext of technical infraction in presentation of the candidate lists. It cannot be excluded that this infringement was made by the electoral commission deliberately in the event leftists would win the elections. The repeat election was scheduled on November 10. Representatives of non-socialist forces in order to avoid errors made during the first election merged into a single bloc that eventually won and got the majority of seats. During both election campaigns, socialists put the blame on authorities for intervention in the election process and even expressed suspicion that the returns were falsified though there was no direct proofs of the last assumption. In their turn, right-wing and moderate forces charged socialists with demagogy, stirring of class struggle and setting “proletarians” on “bourgeois”. In spite of stormy discussion in press, residents of Stavropol remained unconcerned as evidenced by a very low turnout. Stavropol election campaigns in  autumn 1919  were the most scandalous for the whole period of municipal elections on territories controlled by the South Russian White movement. The article goes into details of the course of both campaigns, characterizes electoral lists, presents voting returns, including by city districts, and examples of propaganda materials.